1991
DOI: 10.1128/aem.57.4.1121-1127.1991
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic N-halamines on selected membrane functions in intact Staphylococcus aureus cells

Abstract: Two N-halamine compounds, 3-chloro-4,4-dimethyl-2-oxazolidinone and 1,3-dichloro-4,4,5,5-tetramethyl-2imidazolidinone, were compared with free chlorine as to their effects on selected membrane functions of intact Staphylococcus aureus cells. Free chlorine was found to cause a loss of permeability control, as measured by the efflux of potassium from the cells and a dramatic increase in hydrogen ion permeability, and to affect cell respiration in a nonreversible fashion, as measured by oxygen uptake. The two N-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In conclusion, in the studies in which the toxic effects of lipophilic compounds have been analyzed in some detail, effects on the cytoplasmic membrane and/or membrane-embedded enzymes have been demonstrated (3,124,128,228,275,276,320,321,347). Furthermore, the inhibitory action is in most cases directly related to the partitioning behavior of the lipophilic compounds in n-octanol/water, again suggesting that the (cytoplasmic) membrane is the primary site of toxic action.…”
Section: Other Lipophilic Compoundsmentioning
confidence: 95%
See 1 more Smart Citation
“…In conclusion, in the studies in which the toxic effects of lipophilic compounds have been analyzed in some detail, effects on the cytoplasmic membrane and/or membrane-embedded enzymes have been demonstrated (3,124,128,228,275,276,320,321,347). Furthermore, the inhibitory action is in most cases directly related to the partitioning behavior of the lipophilic compounds in n-octanol/water, again suggesting that the (cytoplasmic) membrane is the primary site of toxic action.…”
Section: Other Lipophilic Compoundsmentioning
confidence: 95%
“…Applications of lipophilic compounds as disinfectants range from soaps and detergents to antiseptics used in facilities for potable water (347) and agents used to prevent biodeterioration. Since the beginning of this century, compounds with a wide antimicrobial spectrum have been used as disinfectants (20,306); these include coal tar liquids (such as tetralin and decalin), lysol-type disinfectants (cresols), chlorinated compounds, and quaternary ammonium compounds (315).…”
Section: Other Lipophilic Compoundsmentioning
confidence: 99%
“…[16][17][18] Thanks to these attractive properties, Nhalamine structures have been incorporated into different materials to provide potent, durable, and rechargeable biocidal functions against a broad spectrum of microorganisms. 17,[19][20][21][22][23][24][25][26][27][28][29][30][31] We found that upon chlorination treatment with diluted sodium hypochlorite bleach, some of the amino groups of chitosan were transformed into Nhalamines. The chlorinated chitosan provided potent antimicrobial activity against both gram-negative and gram-positive bacteria, and effectively prevented the formation of biofilms.…”
Section: Introductionmentioning
confidence: 94%
“…Thus, the biocidal properties of N-halamines can be retained indefinitely [3]. The antimicrobial mechanism of N-halamines against microorganisms is considered to be a direct contact of positive halogen from the N-halamine transferred to the proper reacting site of microorganisms causing inactivation [8,9]. The primary advantages of these compounds are that they are rechargeable and are strong biocides against microorganisms.…”
mentioning
confidence: 99%